2005
DOI: 10.1097/01.sap.0000175483.35073.ea
|View full text |Cite
|
Sign up to set email alerts
|

Improved Flap Viability With Site-Specific Delivery of Sildenafil Citrate Using Fibrin Glue

Abstract: Sildenafil is a cyclic guanosine-specific phosphodiesterase type 5 (PD-5) inhibitor that is widely used for erectile dysfunction. Potent and competitive inhibition of PD-5 enhances levels of cyclic guanosine monophosphate (cGMP). Fibrin glue-apart from tissue fixation-has been used for slow release of drugs. In this study, local delivery of Sildenafil citrate with fibrin glue was accomplished to improve random flap survival. Fifty Wistar rats were randomized into 5 groups, and a standardized dorsal random-patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 45 publications
(84 reference statements)
0
41
0
3
Order By: Relevance
“…Using a rat dorsal random-pattern skin flap, administration of sildenafil in fibrin glue resulted in a significant decrease in flap necrosis, suggesting that topical sildenafil application improves flap survival in rat models (30). In a similar study (31), distally based dorsal skin flaps investigating sildenafil showed dose-dependent effects on random flap survival in rats, with higher doses and shorter intervals increasing efficacy.…”
Section: Sildenafil In Ischemic Animal Studiesmentioning
confidence: 77%
“…Using a rat dorsal random-pattern skin flap, administration of sildenafil in fibrin glue resulted in a significant decrease in flap necrosis, suggesting that topical sildenafil application improves flap survival in rat models (30). In a similar study (31), distally based dorsal skin flaps investigating sildenafil showed dose-dependent effects on random flap survival in rats, with higher doses and shorter intervals increasing efficacy.…”
Section: Sildenafil In Ischemic Animal Studiesmentioning
confidence: 77%
“…Although the main indication of PDE-5 inhibitors is ED, the effectiveness of sildenafil in hypertensive cardiomyopathy [15] , pulmonary hypertension [16] , and renal damage via the NO pathway [17] has been reported previously. The favorable effects of PDE-5 usage on several tissues and organs, such as in flap survival and trans- planted and other organs, have been recently reported [18][19][20] . These new indications and the usage profile of these drugs led us to investigate their efficacy on I/R injury of the testis.…”
Section: Discussionmentioning
confidence: 99%
“…Omiderm accelerates the keratinocyte proliferation process by accumulating under the exsudate and thereby upregulating the epithelisation process as well as protecting the wound from being infected by the environment (16). Nitric oxide (NO) has been discovered in 1980's and it's effects on wound healing has been extensively studied over the past decades (29)(30)(31). NO is synthetized by many types of cells and acts in neurotransmission, regulating the immune system, vessel smooth muscle relaxation and decreasing platelet aggregation to name a few of the properties.…”
Section: Discussionmentioning
confidence: 99%